Describing and identifying various constraints of participating in outdoor recreation activities among female students / Hellinda Marius, Mohd Khairulanwar Md Yusof and Chee Hian Tan - Marius, Hellinda; Md Yusof, Mohd Khairulanwar; Tan, Chee Hian (Universiti Teknologi MARA, 2021)
The purpose of this study was to describe and identify various constraints of participating in outdoor recreation activities among female students of Universiti Teknologi MARA, Perlis. This study examined on the structural and intrapersonal factors. 150 respondents selected convenience at UiTM Perlis. The respondents were based on their education level, 75 for diploma and 75 for bachelor. Result showed that the highest mean for structural constraint was economic (M = 2.67) where else the highest mean for intrapersonal constraint was physical (M = 2.17). This finding also showed that there was no significance differences for structural constraints based on education level but there were significance differences for intrapersonal constraints based on education level: ‘Motivation’ (t =-7.03, p < 0.05), ‘Psychological’ (t = -6.31, p < 0.05) and ‘Physical’ (t = -4.77, p < 0.05) respectively. In conclusion this study expected to enhance as guide to the related parties concerned for overcoming the structural and intrapersonal constraints that influenced participating of recreational activities among female students specifically in UiTM Perlis. Hence, this study provided valuable factors that contributed as constraints among females as scope of interest to University and Ministry Youth and Sport in the future recreational phenomena of constraints to females participating in outdoor recreation activities as a whole nationwide.